2001
DOI: 10.1063/1.1361258
|View full text |Cite
|
Sign up to set email alerts
|

Onset of ferromagnetism in Fe epitaxially grown on GaAs(001) (4×2) and (2×6)

Abstract: Ultrathin Fe films were epitaxially grown at room temperature on GaAs(001) with either predominant (4×2) or (2×6) surface reconstruction. At nominal Fe coverages of tFe⩾2.8 monolayers (ML), a ferromagnetic state is observed below a certain critical temperature, TC. Surprisingly, the magnetic phase transition at TC appears even sharper than for Fe films on metallic single-crystal substrates, which were believed to be an excellent representation of two-dimensional (2D) ferromagnets. This may be due to the extrem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
46
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 11 publications
5
46
0
1
Order By: Relevance
“…Furthermore, at the point of coalescence, the thickness lies above 20 nm for electrodeposition, 10 in stark contrast to about 3 atomic layers for MBE. 16 Therefore, most studies on electrodeposited Fe on GaAs [8][9][10][11][12][13] have focused on the fabrication of films of several 100 nm, and the structural, magnetic 12 and spin transport characterization 13 of these. Recently, we demonstrated that epitaxial Fe nanocuboids can be achieved when the deposition is stopped prior to coalesce of the nuclei in a lower-concentration electrolyte with reduced deposition rate.…”
mentioning
confidence: 99%
“…Furthermore, at the point of coalescence, the thickness lies above 20 nm for electrodeposition, 10 in stark contrast to about 3 atomic layers for MBE. 16 Therefore, most studies on electrodeposited Fe on GaAs [8][9][10][11][12][13] have focused on the fabrication of films of several 100 nm, and the structural, magnetic 12 and spin transport characterization 13 of these. Recently, we demonstrated that epitaxial Fe nanocuboids can be achieved when the deposition is stopped prior to coalesce of the nuclei in a lower-concentration electrolyte with reduced deposition rate.…”
mentioning
confidence: 99%
“…Superparamagnetic behaviour has not been universally observed, however. In other work, 31,34 observations of a reduction in Curie temperature for ultra thin Fe films on GaAs suggest that this effect, in agreement with the behaviour exhibited by ultra thin magnetic films grown on metallic substrates [ref], could be the main reason for the absence of a ferromagnetic response at RT.…”
Section: Introductionmentioning
confidence: 66%
“…Various groups have explored this behaviour using a variety of techniques and have delivered results for the onset ranging from a few ML up to values as high as 10.5ML. [30][31][32][33][34][35][36][37][38][39] Aside from compound formation, it has been suggested that this deferment of ferromagnetic character is heavily dependent on the 3-D growth morphology of the developing Fe overlayer. In an in-situ study 32 the evolution of the magneto optical Kerr effect (MOKE) signal with Fe coverage was attributed to the existence of a superparamagnetic phase sandwiched between nonmagnetic (below 3.5 ML coverage) and ferromagnetic (4.8 ML +) phases in the growth of Fe films on GaAs at room temperature (RT).…”
Section: Introductionmentioning
confidence: 99%
“…Among the different experimental methods the measurement of the susceptibility χ(T ) is a very powerful method for the analysis of thin film systems [1,2]. The maximum of the susceptibility corresponds to the occurrence of a nonvanishing magnetization for the temperatures below the Curie temperature T C .…”
Section: Model and Methodsmentioning
confidence: 99%